Enhancing the Professional Capacity of Islamic Religious Education Teachers in Developing KOSP through a PAR-Based Mentoring Program in North Lampung - Kurniawan, Muklis; Januri; Tanjung, Erwin; Wulan Sari, Oppi; Syarifuddin Zuhri, Ahmad (LP2M INSURI Ponorogo, 2025)
This community service activity aims to strengthen the professional capacity of Islamic Religious Education (PAI) teachers in developing the Operational Curriculum for Educational Units (KOSP) based on the Independent Curriculum in North Lampung Regency. This activity was motivated by teachers' limited ability to compile KOSP documents, Learning Objective Flows (ATP), and contextual teaching modules aligned with the principles of independent learning. The Participatory Action Research (PAR) approach was implemented as a participatory mentoring model, positioning PAI teachers as active partners throughout the problem identification, implementation, reflection, and evaluation processes. This program involved PAI teachers from 20 educational units and was implemented through structured activities, including socialization, interactive training, collaborative KOSP and ATP workshops, ongoing mentoring, and joint reflection. The results of the community service demonstrated improvements in teachers' curriculum development practices, as participants were able to produce school-based KOSP documents, design systematic ATP aligned with learning outcomes, and develop contextual and differentiated PAI teaching modules tailored to student characteristics and the local context. In addition, the mentoring process fostered increased self-confidence, collaboration, and reflective awareness. The uniqueness of this activity lies in the PAR-based mentoring design, which emphasizes active involvement, collaborative learning, and sustainability.